The stickiness of food prices in Poland – online vs. Traditional shops - Jaworski, Krystian (Publishing House of Wroclaw University of Economics and Business, 2022)
The author calculated various measures of price stickiness of food products in online shops and compared them with their counterparts in traditional shops in Poland. The main findings are as follows: (1) food prices in online shops are less sticky than in traditional shops; (2) the scale of percentage price changes is also smaller in online shops, and price increases and price decreases are both smaller in absolute terms compared to traditional stores; (3) price stickiness increases and the scale of price change decreases if the impact of promotions is eliminated; and (4) using daily data leads to lower estimates of price stickiness and a greater scale of percentage change in prices compared to monthly data, thus indicating that intra-month price changes are common in online shops. These findings may have significant policy implications if declining price stickiness in online shops (observed in the case of food products) also occurs in other product categories, as it would mean that the overall price rigidity in Poland has decreased over time. In the DSGE-New Keynesian approach, such results would indicate a decrease in the transmission of monetary policy shocks to the real economy and represent an important contribution to understanding the monetary transmission mechanism in Poland.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 291-311
Keywords: monetary transmission; Internet; DSGE; Keynesian